2020
DOI: 10.1007/s00068-020-01524-9
|View full text |Cite
|
Sign up to set email alerts
|

More medications, more problems: results from the Sedation Level after Emergent Exlap with Packing for TRAUMA (SLEEP-TRAUMA) study

Abstract: Purpose Sedation management of trauma patients after damage control laparotomy (DCL) has not been optimized. We evaluated if shorter sedation exposure was associated with increased proportion of delirium-free/coma-free (DF/CF-ICU) days and change in time to definitive fascial closure (DFC). Methods We reviewed trauma DCL patients at an ACS-verified level I center over 5 years as shorter (SE) or longer than median (LE) sedation exposure. We compared demographics, injury patterns, hemodynamic parameters, and inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In our multivariable linear regression analysis, the only two commonalities identified among those listed above were the use of paralytic and dexmetomidine infusions as risk factors associated with decreased DF/CF-ICU-30. This corroborates single-institution data recently published by Kim et al demonstrating that longer exposure to sedation in trauma patients after DCL was associated with a reduction in DF/CF-ICU-30 [22]. Other studies have shown that deeper levels of sedation and longer exposure to sedation has been linked to worse ICU outcomes, but not specifically to delirium.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our multivariable linear regression analysis, the only two commonalities identified among those listed above were the use of paralytic and dexmetomidine infusions as risk factors associated with decreased DF/CF-ICU-30. This corroborates single-institution data recently published by Kim et al demonstrating that longer exposure to sedation in trauma patients after DCL was associated with a reduction in DF/CF-ICU-30 [22]. Other studies have shown that deeper levels of sedation and longer exposure to sedation has been linked to worse ICU outcomes, but not specifically to delirium.…”
Section: Discussionsupporting
confidence: 91%
“…The primary endpoint was DF/CF-ICU-30, defined as the number of ICU days out of the first 30 ICU days during which the RASS was at least -3 and the CAM-ICU score was negative divided by the total number of ICU days for each patient and converted to a percentage. The intent of this measure is to serve as a surrogate marker of freedom from delirium, calculated in a manner that avoids bias from varying lengths of ICU stay, previously published by Kim, et al [22] Furthermore, our measure was censored at 30 days to account for the fact that, for the purposes of our study, it was only feasible to collect ICU data for the first 30 days of the patient's ICU stay [22]. Due to the significant differences in mechanisms, patients were grouped as trauma (T) or nontrauma (NT) for purposes of analysis.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A single-center review of delirium in T patients after DCL indicated a very high incidence of delirium in this population, as well as revealing a negative association between the duration of sedation infusion exposure and the proportion of delirium-free/coma-free ICU days. 45 It is interesting to see, therefore, that the incidence of delirium in the T cohort is even higher than in the NT cohort, despite the T cohort being younger and the mortality and ICU utilization being similar. One key factor unique to the T cohort is traumatic brain injury.…”
Section: Discussionmentioning
confidence: 96%
“…Much has been made of the use of neuromuscular blockade to facilitate more rapid achievement of PFC, although the most recent data do not support this assertion [28]. We previously published singlecenter data indicating that shorter duration of sedation infusions was associated with reduced time to PFC in trauma patients [29]. In this larger multicenter study of both trauma and non-trauma patients, we did not find that the duration of benzodiazepine, propofol, dexmedetomidine, or paralytic infusions was associated with the likelihood of achieving PFC.…”
Section: Discussionmentioning
confidence: 99%